Peran OKI dalam Konflik Mindanao - Muhammad, Muhammad Awwab (Jurnal Ilmu Hubungan Internasional LINO, 2024)
The conflict in Mindanao, Philippines, has attracted international attention because of its broad social, political and humanitarian implications. The Organization of Islamic Cooperation (OIC) has played a significant role in trying to mediate and defuse tensions in the region. This article analyzes the role of the OIC in the context of the Mindanao conflict, with a focus on mediation and peacebuilding efforts. Through a qualitative approach, we investigate the OIC's initiatives in facilitating dialogue between parties involved in the conflict, as well as their support in promoting social and economic development to support sustainable peace. By combining a literature review with primary data, this article identifies the challenges faced by the OIC in carrying out its role and evaluates its impact in influencing conflict dynamics. The findings highlight the OIC's important role in strengthening the peace process in Mindanao, while highlighting areas where further efforts can be improved. The implications of this analysis contribute to a better understanding of the role of regional organizations in conflict resolution and provide guidance for future strategies in promoting stability and peace in Mindanao and similar regions.